1986
DOI: 10.1126/science.3704640
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Drug Stereoisomers by the Formation of β-Cyclodextrin Inclusion Complexes

Abstract: For many drugs, only racemic mixtures are available for clinical use. Because different stereoisomers of drugs often cause different physiological responses, the use of pure isomers could elicit more exact therapeutic effects. Differential complexation of a variety of drug stereoisomers by immobilized beta-cyclodextrin was investigated. Chiral recognition and racemic resolution were observed with a number of compounds from such clinically useful classes as beta-blockers, calcium-channel blockers, sedative hypn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
229
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(238 citation statements)
references
References 19 publications
5
229
0
3
Order By: Relevance
“…One drawback to the host-guest route is the lack of a generic process, meaning that each recognition problem requires a novel solution. Approaches that utilize naturally occurring macromolecules to act as selective recognition sites are well documented (6).…”
Section: Introductionmentioning
confidence: 99%
“…One drawback to the host-guest route is the lack of a generic process, meaning that each recognition problem requires a novel solution. Approaches that utilize naturally occurring macromolecules to act as selective recognition sites are well documented (6).…”
Section: Introductionmentioning
confidence: 99%
“…环糊精(Cyclodextrin, CD)是一种具有特殊疏水空腔 的非还原性天然寡糖, 能与多种无机或有机分子形成稳 定的主体-客体包合物, 且多个手性 C 原子构成了良好 的不对称环境, 使其在分离对映体方面取得一系列成 果 [8] . 目前应用广泛的大都是基于天然或改性环糊精的 单一型手性固定相以及于新型功能键合臂的开发, 虽然 制备出了一系列优秀的单层环糊精手性固定相, 但是性 能优异的新型环糊精固定相的数目正在减少, 这成为手 性分离技术发展的瓶颈 [9] .…”
Section: 引言unclassified
“…Armstrong et al (28) have shown that enantiomers of metoprolol, hexobarbital, methadone and many more drugs can be separated by this stationary phase, however enantiomers of certain drugs, such as chlorcyclizine and bupivacaine, are not effectively resolved, presumably due to the absence of differential interaction with the rim of the CD cavity. One further advantage of CD phases is that they are relatively cheaper than the other CSPs.…”
Section: Cyclodextrin Bonded Phasesmentioning
confidence: 99%